2008
DOI: 10.1086/591458
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelets AttenuateAspergillusSpecies via Granule‐Dependent Mechanisms

Abstract: Using laser scanning microscopy, we investigated whether platelets are capable of internalizing Aspergillus conidia and examined Aspergillus-platelet adherence. The influence of platelets on fungal growth was evaluated by assessing galactomannan (GM) release, hyphal elongation, and colony size. A secretion assay with [3H]-serotonin (5-hydroxytryptamine [5-HT]) was performed. Exposure to platelets resulted in significantly decreased GM release (P<.05), hyphal elongation (P<.001), colony size, pig-mentation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 13 publications
4
65
0
1
Order By: Relevance
“…Previous evidence was obtained for an interaction between platelets and the cell wall of C. albicans but the triggering molecules of this pathogenic yeast were not identified (29,33). During invasive fungal infection, C. albicans-derived cell wall components, including ␤-1,3 glucans, are known to circulate in patients' sera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous evidence was obtained for an interaction between platelets and the cell wall of C. albicans but the triggering molecules of this pathogenic yeast were not identified (29,33). During invasive fungal infection, C. albicans-derived cell wall components, including ␤-1,3 glucans, are known to circulate in patients' sera.…”
Section: Discussionmentioning
confidence: 99%
“…act with platelets in circulating blood (33). This interaction between the fungus and the host occurs at the level of the cell wall, which consists mainly of polysaccharides associated with proteins and lipids (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets bind plasma-opsonized hyphae and degranulate (42). The interaction of platelets with hyphae results in reduced hyphal galactomannan release, impaired hyphal elongation, and loss of hyphal wall integrity, and these effects were inhibited when granule exocytosis was blocked (42,123). Serotonin, a component of platelet granules, has also been found to kill both conidia and hyphae and to induce damage to fungal cell membranes (88,124).…”
Section: Plateletsmentioning
confidence: 99%
“…Furthermore, it has been reported that liver transplant recipients with thrombocytopenia have a considerably higher incidence of fungal infection than nonthrombocytopenic patients (3). There are some reports on the interaction between A. fumigatus and platelets, showing inhibition of fungal growth potentially involving the release of known plateletderived microbial peptides, as well as direct physical interaction between platelets and conidia or hyphae (4,16).…”
mentioning
confidence: 99%